Functionalized magnetic nanosized materials for efficient biodiesel synthesis via acid-base/enzyme catalysis - Wang, Anping; Sudarsanam, Putla; Xu, Yufei; Zhang, Heng; Li, Hu; Yang, Song (Green Chemistry, 2020)
According to the principles of green chemistry, the rapid recovery and reuse of catalysts after a catalytic reaction are important factors to realize the sustainable management of chemical production processes. The functionalization of magnetic nanoparticles is the basis for the efficient separation of heterogeneous catalysts from the reaction system by using the magnetic separation technology as well as for effectively bridging heterogeneous and homogeneous catalytic processes. This can considerably improve the production efficiency and reduce energy consumption as well. Owing to important applications as a potential biofuel or fuel additive, the synthesis of biodiesel mainly from low-cost biomass feedstocks has received considerable attention in the current biorefinery research. A simple synthesis process coupled with the application of functionalized magnetic catalysts can remarkably reduce the production cost and minimize waste generation, thereby promoting the potential development of green catalytic processes for the large-scale synthesis of biodiesel. In this review, the preparation methods, structural and performance control, and protection and functionalization of magnetic nanoparticles as well as the consequent catalytic effects in the synthesis of biodiesel (mainly long-chain fatty acid methyl esters) have been reported. In addition, various representative reaction mechanisms are discussed, emphasizing the existing challenges and prospects of industrialization.

Sulfonic acid-functionalized heterogeneous catalytic materials for efficient biodiesel production: a review - Tan, Xiang; Sudarsanam, Putla; Tan, Jinyu; Wang, Anping; Zhang, Heng; Li, Hu; Yang, Song (Journal of Environmental Chemical Engineering, 2021)
The development of social productive forces leads to the increasing consumption of fossil fuels. However, the burning of traditional fossil fuels releases huge amounts of carbon emissions into the atmosphere, resulting in drastically increased global surface temperatures, and hence, global warming and abnormal climate change. Biodiesel, which can be produced by (trans)esterification of bio-oils using solid acid catalysts, is recognized as renewable and clean energy, alternative to fossil-derived diesel, and it can meet society's requirements. This review describes the catalytic conversion of bio-derived oils into biodiesel using various sulfonic acid-functionalized heterogeneous catalytic materials that show higher catalytic efficiency and superior recyclability. Besides, various methods of biodiesel preparation and the appropriate design and preparation of robust and efficient catalytic materials for biodiesel production were provided. Finally, the mechanisms of different catalytic esterification and transesterification reactions for biodiesel synthesis, the relevant reaction kinetic models, and techno-economic analysis of biodiesel production were critically discussed in this review.
Keywords: (Trans)esterification; Biodiesel; heterogeneous catalysis; kinetic study; solid acid